The Role of Organizational Learning, Knowledge Sharing, and Innovation Capability on Firm Performance - Anshori, Mochammad Isa; Kamil, Ahmad; Sukardi; Aminah, Siti (Malaqbi Publisher, 2025)
This study investigates the role of organizational learning, knowledge sharing, and innovation capability in influencing firm performance. Drawing on the knowledge-based view and resource-based view, the research examines how these intangible capabilities contribute to organizational success in dynamic and competitive environments. Using a quantitative approach, data were collected from firms across diverse industries and analyzed through multiple regression analysis. The results demonstrate that organizational learning, knowledge sharing, and innovation capability each have a significant positive effect on firm performance, with innovation capability exerting the strongest influence. Furthermore, the findings highlight the synergistic relationship among these variables, indicating that organizational learning and knowledge sharing serve as critical enablers of innovation capability, which in turn drives superior performance outcomes. The study contributes to theoretical discourse by integrating these constructs into a unified framework and provides practical insights for managers on the importance of fostering learning systems, promoting knowledge exchange, and investing in innovation as strategic priorities. Implications, limitations, and directions for future research are also discussed